Peran Generasi Milenial Dalam Mengembangkan Ekonomi Kreatif Di Era Digital - Aisyah Pradyahning Yahya; Betty Silfia Ayu Utami (Jurnal Ekonomi dan Bisnis Digital, 2025)
The creative economy has become one of the important pillars in driving economic growth in the digital era. The millennial generation, with its adaptive characteristics to technology and innovation, plays a key role in the development of this sector. This research aims to analyze the contribution of the millennial generation in developing the creative economy in the digital era, using the literature study method. Data was obtained through literature review from various sources, including scientific journals, books, and related industry reports. The results show that millennials utilize digital technology as a means to create and market creative products, such as art, design, culinary, and digital content. In addition, this generation's ability to build networks through social media and digital platforms has a significant impact on market expansion and increased product added value. However, challenges such as limited access to capital, lack of entrepreneurship training, and intense global competition need to be overcome to support the sustainability of millennials' contribution in the creative economy sector. This study concludes that government and private sector support, such as the provision of training, access to capital, and strengthening digital infrastructure, is needed to maximize the potential of the millennial generation in developing the creative economy.